The Expected and Unexpected Consequences of ESA 2010 - an Irish perspective - Connolly, Michael (Statistical and Social Inquiry Society of Ireland, 2018)
On 14 July 2016 Ireland reported an extraordinary increase in GDP of 26.3% for 2015. This paper explores the rationale for this result in the context of the new statistical standards of SNA 2008 (ESA 2010) and BPM6 that had been recently introduced. The primary focus is on the recording of research and development activities now inside the production boundary and included for the first time in the Macro Economic accounts together with the related contract manufacturing activities. There is particular reference to the impact of economic globalisation, together with initiatives linked to application of the Base Erosion and Profit Shifting (BEPS) recommendations of OECD. The large corporate relocations in 2015 together with transactions in intangible assets and the associated depreciation are explained and their impact on the economic accounts is illustrated. Some unintended consequences of the application of the new statistical standards is discussed and an alternate approach to the recording in particular of cross border transactions in Intellectual Property products is outlined.
read before the Society, 30 November 2017
Keywords: Globalization; System of National Accounts; Research and Development; Depreciation; Balance of Payments; Contract Manufacturing; 314.15